(untitled) (Jurnal Teknologi Industri Pertanian, 2013)
Biomass pellet (biopellet) is a biomass-based solid fuel with tubular solid form which is one of alternative energy for rural community. The abundance of palm shell and palm fiber is a potential source of biomass that can be converted into biopellet. Pelletization can improve the quality and burning characteristics of biomass. The objectives of this research were to study the utilization of palm shell and fiber into biopellet production and to assess the effect of addition of palm shell charcoal and palm fiber. The percentages of palm shell charcoal and palm fiber were 0%, 10%, and 20%. Carbonization process was done by using kiln for ±4.5 hours at 450○C. Densification process was done by using pellet mill whose the capacity of 10 kg/hour with a dies diameter of 15 mm and at temperature of 250○C for 2 minutes of pressure time. The research was started with an analysis of physic-chemical properties of the raw material and then followed by analysis of combustion characteristics. Based on the physic-chemical properties and the combustion characteristics, biopellet of palm shell that contained 80% of palm shell and 20% of palm shell charcoal gave the best quality. It had moisture content of 0.47%, ash content of 9.83%, volatile substances of 55.34%, fixed carbon of 34.84%, heating value of 5,265.92 kcal/kg, bulk density of 1,260.30 kg/m3, and pressure strength of 82.09 kg/cm2. The consumption rate was 1.39 kg/hour and the combustion efficiency was 11.59%. The production of palm shell biopellet on a laboratory scale produced yield of 11.54%. Biopellet increased heating value of palm shell for 15.55%. Keywords: biopellet, palm shell, palm fiber, charcoal, carbonization